2014
DOI: 10.1007/s11356-014-3457-8
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent short-term study of di-n-butyl phthalate on the testicular antioxidant system of Wistar rats

Abstract: Di-n-butyl phthalate (DBP), a xenobiotic, is widely used in industries as a softener for polyvinyl chloride resins. The aim of the present study was to evaluate whether DBP induces oxidative stress in testes of Wistar rats. DBP at doses of 500, 1,000 and 1,500 mg/kg b.wt. (doses below LD50) was given orally for 7 days. After 24 hrs from the last dose, the animals were killed under ether anesthesia. Nonsignificant increase in testicular weight was observed. Histological studies indicated a dose-related degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Moreover, phthalates downregulate the expression of genes required in cholesterol conveyance and testosterone synthesis in male rats (Thompson et al, 2005;Borch et al, 2006). Parallel to this, our results showed that DBP treatment reduced the serum (Nair et al, 2008;Nair, 2015) and testicular testosterone levels. Non-significant changes in the serum levels of LH and FSH were recorded during the 2 time points of study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Moreover, phthalates downregulate the expression of genes required in cholesterol conveyance and testosterone synthesis in male rats (Thompson et al, 2005;Borch et al, 2006). Parallel to this, our results showed that DBP treatment reduced the serum (Nair et al, 2008;Nair, 2015) and testicular testosterone levels. Non-significant changes in the serum levels of LH and FSH were recorded during the 2 time points of study.…”
Section: Discussionsupporting
confidence: 78%
“…These findings were comparable to those described by Alam et al, (2010) and Bao et al, (2011). Nair et al (2008) and Nair (2015) stated similar histopathological results, although they reported atrophy of Leydig cells. Testicular lesions could be ascribed to the rise in MDA production and the resultant lipid peroxidation with advanced reduction in the various spermatogenic cells, as well as degeneration of Sertoli and Leydig cells.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Testes are among the most susceptible organs to stress, heat and environmental pollutants . DBP at a dose of 500 mg/kg d, one‐sixteenth of the median lethal dose, is able to induce lesions in vivo but does not cause death . Our findings demonstrated that treatment with DBP at this dose resulted in apparent toxic effects, including anomalous development of the testes, severe atrophy of the seminiferous tubules and histological disruption of spermatogenesis, which could be attenuated by SFN supplementation.…”
Section: Discussionmentioning
confidence: 65%